The Blood-Brain Barrier and the EphR/Ephrin System: Perspectives on a Link Between Neurovascular and Neuropsychiatric Disorders - Malik, Victoria A.; Di Benedetto, Barbara (Frontiers in Molecular Neuroscience, 2018)
Interactions among endothelial cells (EC) forming blood vessels and their surrounding cell types are essential to establish the blood-brain barrier (BBB), an integral part of the neurovascular unit (NVU). Research on the NVU has recently seen a renaissance to especially understand the neurobiology of vascular and brain pathologies and their frequently occurring comorbidities. Diverse signaling molecules activated in the near proximity of blood vessels trigger paracellular pathways which regulate the formation and stabilization of tight junctions (TJ) between EC and thereby influence BBB permeability. Among regulatory molecules, the erythropoietin-producing-hepatocellular carcinoma receptors (EphR) and their Eph receptor-interacting signals (ephrins) play a pivotal role in EC differentiation, angiogenesis and BBB integrity. Multiple EphR-ligand interactions between EC and other cell types influence different aspects of angiogenesis and BBB formation. Such interactions additionally control BBB sealing properties and thus the penetration of substances into the brain parenchyma. Thus, they play critical roles in the healthy brain and during the pathogenesis of brain disorders. In this mini-review, we aim at integrating the constantly growing literature about the functional roles of the EphR/ephrin system for the development of the vascular system and the BBB and in the pathogenesis of neurovascular and neuropsychiatric disorders. We suggest the hypothesis that a disrupted EphR/ephrin signaling at the BBB might represent an underappreciated molecular hub of disease comorbidity. Finally, we propose the possibility that the EphR/ephrin system bears the potential of becoming a novel target for the development of alternative therapeutic treatments, focusing on such comorbidities.